Supplier switching versus supplier development under risk: A mathematical modelling approach. (December 2021) - Jafarian, Mahdi; Lotfi, M.M.; Pishvaee, Mir Saman
Highlights: Mathematical modeling for dealing with problematic suppliers under risk. Proposing lost market share to evaluate risk considering QCD measures. Generating decision matrix as a tool to guide preferable decision under risk. The decision is highly dependent on the risk aversion level of decision maker. Variation of investment cannot change the development decision from risky to safe. Abstract: In this study a mathematical modeling approach is proposed to deal with problematic suppliers under risk. The decisions to make include a) developing the incumbent supplier to improve its performance (development), b) switching to an appropriate alternative supplier (switching), and c) continuing with the incumbent supplier (status quo). The lost market share is proposed as a novel variable to evaluate decision risks considering the core performance measures of quality, cost, and delivery. The problem is encountered with two important uncertain parameters including investment-improvement coefficient and alternative supplier performance scores. A comprehensive analysis is conducted based on the uncertain parameters and decision risks at different confidence levels. As the results indicate, the decision is highly dependent on the risk aversion level of the decision maker. Furthermore, the risk of the development decision is independent of the current performance of the incumbent supplier and the desired performance of the buyer. Inversely, the risk of the switching decision depends on the current performance of the incumbent supplier. It is also found that the variation coefficient of the investment-improvement parameter plays a critical role in the development decision. Finally, a decision matrix is developed as a decision support tool for managerial guidelines regarding preferable decisions from the risk point of view.